2010
DOI: 10.1186/1471-2474-11-185
|View full text |Cite
|
Sign up to set email alerts
|

The influence of long-term treadmill exercise on bone mass and articular cartilage in ovariectomized rats

Abstract: BackgroundLoss of bone quality and deterioration of articular cartilage are commonly seen after menopause. While exercise may protect against tissue degeneration, a clear link has yet to be established. The aim of the present study is to investigate the influence of long-term treadmill exercise on changes in bone mass and articular cartilage in ovariectomized rats.MethodsSixty female Sprague-Dawley rats were randomly assigned to 4 groups: ovariectomized (OVX), ovariectomized plus treadmill exercise (OVX-RUN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
1
16
0
5
Order By: Relevance
“…This finding might be attributed to the position of tibia and mechanical loading on the tibia during treadmill running (Iwamoto et al, 2011;Mosavian 2017). Moreover, Chang et al (2010) showed that the cancellous bone response to exercise changes relative to the bone mechanical loading. This finding is consistent with a previous study, which indicated the positive site-specific effect of treadmill exercise on BMD, with predominant weight-bearing sites (Iwamoto et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding might be attributed to the position of tibia and mechanical loading on the tibia during treadmill running (Iwamoto et al, 2011;Mosavian 2017). Moreover, Chang et al (2010) showed that the cancellous bone response to exercise changes relative to the bone mechanical loading. This finding is consistent with a previous study, which indicated the positive site-specific effect of treadmill exercise on BMD, with predominant weight-bearing sites (Iwamoto et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Serial longitudinal sections were cut with a rotary microtome and mounted on saline-coated slides glass after preparation of histological specimens. Before staining, the sections were deparaffinized in 100% xylene and rehydrated in graded ethanol (Chang et al, 2010). The longitudinal sections of the proximal tibia, between medial and lateral intercondyloid spines, and transvers sections of the mid shaft of tibia were cut at 5-µm thickness with a microtome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Del Carlo et al 23 realizaram um estudo com ratos imobilizados por 45 dias e remobilizados livre e por meio de exercício físico, no qual os animais que realizaram natação demonstraram quadro menos severo de lesão no tecido cartilaginoso, demonstrada por análise histológi-ca. Chang et al 24 evidenciaram que o exercício físico promove uma proteção aos condrócitos mesmo em ratas que foram submetidas à ovariectomia, condição que pode acelerar o processo de degeneração da cartilagem, mantendo assim sua integridade estrutural.…”
Section: Discussionunclassified
“…Для этого образцы фиксировали в 10% растворе нейтрального формалина, декальцинировали и заливали в парафин. Критериями гистологической оценки служили изменения околосустав-ного аппарата, наличие воспалительного инфильтрата, состояние суставного хряща и костной ткани [29]. Состояние хряща по каждому из этих критериев оценивали в баллах так, что при максимальной выраженности патологического Окрашивание гематоксиллином и эозином…”
Section: потенцирование регенеративных процессов хряща и эффективностunclassified